Development of a risk scoring system for patients with papillary thyroid cancer. Issue 4 (7th February 2019) - Pak, Kyoungjune; Kim, Yun Hak; Suh, Sunghwan; Goh, Tae Sik; Jeong, Dae Cheon; Kim, Seong Jang; Kim, In Joo; Han, Myoung‐Eun; Oh, Sae‐Ock
Abstract: As the importance of personalized therapeutics in aggressive papillary thyroid cancer (PTC) increases, accurate risk stratification is required. To develop a novel prognostic scoring system for patients with PTC (n = 455), we used mRNA expression and clinical data from The Cancer Genome Atlas. We performed variable selection using Network‐Regularized high‐dimensional Cox‐regression with gene network from pathway databases. The risk score was calculated using a linear combination of regression coefficients and mRNA expressions. The risk score and clinical variables were assessed by several survival analyses. The risk score showed high discriminatory power for the prediction of event‐free survival as well as the presence of metastasis. In multivariate analysis, the risk score and presence of metastasis were significant risk factors among the clinical variables that were examined together. In the current study, we developed a risk scoring system that will help to identify suitable therapeutic options for PTC.